Development of a duplex chamber digital PCR to quantify twelve genetically modified maize events - Eun-Ha Kim; Youn-Sung Cho; Byeori Kim; Yelinn Yoo; Jae-In Lee; Young Soon Kim; Tae-Sung Park (GM Crops & Food)
Accurate quantification of genetically modified organisms (GMOs) is essential for regulatory compliance, especially under threshold-based labeling policies. In this study, we developed and validated twelve event-specific duplex chamber- or chip-based digital PCR (cdPCR) methods using microfluidic array plates to quantify GM maize events approved in South Korea. In contrast to conventional real-time PCR, the cdPCR approach allows for absolute quantification without standard curve calibration and incorporates event-specific zygosity ratio correction to improve accuracy of the measurement. The method was evaluated at GMO content levels of 0.9%, 3.0%, and 5.0%. It demonstrated high sensitivity and robustness, with trueness, precision, and reproducibility satisfying the minimum performance criteria recommended by international guidelines. Comparative analysis with real-time quantitative PCR (qPCR) showed comparable accuracy; however, cdPCR provided advantages in cost-efficiency and operational simplicity. These findings support the applicability of duplex cdPCR as a practical and reliable tool for GMO quantification, particularly in national regulatory laboratories and for enforcement of labeling thresholds such as Korea’s 3.0% rule.